Strategies for solving administrative problems using machine learning technology on Amazon - Alsuhaimi, Rana Mohammed; Aldhafeeri, Shomoukh Abdullah; Alotaibi, Maha Mohammed; Othman, Futoon Ahmed (Journal of Economic, Administrative and Legal Sciences, 2025)
This study's goal is to determine how using machine learning technology has in impact in solving management problems on Amazon. and the study addressed the use of machine learning technology in every step of management problem-solving strategies, the problem of the study is revolves around knowing the strategies for solving administrative problems in business organizations, and the importance of the study is that it is - according to the knowledge of researchers - one of the first Arab studies that deal with the impact of machine learning technology in solving administrative problems on Amazon.The study relied on content analysis by analyzing Amazon's website to arrive at the most prominent use of machine learning technology in problem solving as well as intellectual production analysis to build the checklist tool.One of the most crucial findings is that the impact of using machine learning technology to solve management problems on Amazon using the checklist tool to come up with the use of machine learning technology in every step of resolving management problems The study found a positive impact of the use of machine learning technology in solving Amazon's management problems for its role in saving time and effort on users involved in solving these problems. Amazon offers machine learning technologies as products for all other organizations to leverage in streamlining and facilitating management problem solving The study recommended the integration of smart technologies such as machine learning and others into management problems in organizations according to the strategies followed, The study also recommends that Arab studies should adopt the subject of management problem-solving strategies and integrate them with modern techniques because of the lack of Arab studies in the field of research.
Keywords: Amazon; Machine Learning; Management Problem Solving Strategy; Problem Solving; Strategy